2011
DOI: 10.1074/jbc.m110.202135
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Urokinase Plasminogen Activator (uPA)-mediated Atherosclerosis

Abstract: Data from clinical studies, cell culture, and animal models implicate the urokinase plasminogen activator (uPA)/uPA receptor (uPAR)/plasminogen system in the development of atherosclerosis and aneurysms. However, the mechanisms through which uPA/uPAR/plasminogen stimulate these diseases are not yet defined. We used genetically modified, atherosclerosis-prone mice, including mice with macrophage-specific uPA overexpression and mice genetically deficient in uPAR to elucidate mechanisms of uPA/uPAR/plasminogen-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 65 publications
1
39
0
3
Order By: Relevance
“…In addition, the shear stress acting on the vein may have increased. These physical and chemical factors could have resulted in apoptosis and stimulated VSMCs in the vessel walls to migrate to the intima (Farris et al, 2011). This may explain the early apoptosis and decline in tunica medial-adventitial thickness observed in the present work following transplantation.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In addition, the shear stress acting on the vein may have increased. These physical and chemical factors could have resulted in apoptosis and stimulated VSMCs in the vessel walls to migrate to the intima (Farris et al, 2011). This may explain the early apoptosis and decline in tunica medial-adventitial thickness observed in the present work following transplantation.…”
Section: Discussionsupporting
confidence: 67%
“…Farris et al (2011) observed that plasminogen activators, particularly urinary plasminogen activator (uPA), and their receptors play significant roles in vein graft restenosis (Castro and Tanus-Santos, 2013). uPA also facilitates the expression of matrix metalloproteinases (MMPs).…”
Section: Discussionmentioning
confidence: 99%
“…42 In a mouse transgenic model, macrophage-specific uPA overexpression accelerated atherosclerosis by stimulation of lesion progression and accumulation of lipids in early lesions, and these effects were largely independent of uPAR. 43 However, in the absence of uPA overexpression, uPAR contributed modestly to atherosclerosis. Our study suggests that the uPA-uPAR interaction may be an important contributor to atherogenesis, and the increased serum PON1 activity and decreased oxidative stress shown in uPAR Ϫ/Ϫ mice could account, at least in part, for the reported resistance of low-density lipoprotein receptor Ϫ/Ϫ / uPAR Ϫ/Ϫ double knockout mice to high-fat diet-induced atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that the uPA-uPAR interaction may be an important contributor to atherogenesis, and the increased serum PON1 activity and decreased oxidative stress shown in uPAR Ϫ/Ϫ mice could account, at least in part, for the reported resistance of low-density lipoprotein receptor Ϫ/Ϫ / uPAR Ϫ/Ϫ double knockout mice to high-fat diet-induced atherosclerosis. 43 In summary, this study has important implications for understanding the ability of uPA to modulate oxidative stress, and it gives more insight into the influence of uPA on atherogenesis. .…”
Section: Discussionmentioning
confidence: 99%
“…Animals were fed a western high-fat diet to develop complex atherosclerotic plaques in the sinus of Valsalva of the aorta. Previously, it has been shown that apolipoprotein E deficient and LDLR -/ -mice have significantly more calcified aortic areas than nontransgenic mice [29] and that uPAR is atherogenic in nontransgenic LDLR -/ -mice [30]. Furthermore, it was demonstrated that uPAR deficiency results in impaired vascular inflammation and remodeling [23,31].…”
Section: Upar Mediates C5ar Expression and Vascular Calcification Inmentioning
confidence: 99%